Pengaruh Beban dan Lingkungan Kerja Terhadap Kejadian Medication Administration Error (Studi Kuantiatif di RSKD Dadi Provinsi Sulawesi Selatan) - Muhammad Arief Kusuma; Erliany Syaodih; Kahar Mulyani (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2026)
This study analyzes the effects of workload and work environment on Medication Administration Errors at RSKD Dadi Hospital, South Sulawesi. A quantitative cross sectional design was applied using linear regression analysis. Data were collected from healthcare workers through structured questionnaires. The results show that workload has a positive and significant effect on Medication Administration Errors, indicating that higher workload increases the risk of errors in medication administration. The work environment also shows a significant effect, where better physical and non physical conditions are associated with a lower incidence of errors. These findings highlight the importance of balanced workload management and supportive work environments to improve patient safety. Practical implications include optimizing staff allocation, improving work conditions, and strengthening medication safety systems to reduce medication administration errors in hospital settings.